A robust wireless OFDM echo cancellation system - Bernhardt, Micael (2013)
In this paper, we introduce an echo cancellation technique for full-duplex wireless Orthogonal Frequency Division Modulation (OFDM) communication. The novelty of the work is related to improvements in the models to compensate far-end channel and transmitter front-end, not considered before. Interference cancellation is based on Least Squares (LS) algorithm performed in two successive stages, while far-end channel estimation is accomplished by a training symbol. Using simulation results, we show that the self-interference suppression achieved by our technique increases the system capacity up to levels close to the equivalent of a transmission without interference.